Gender differences in within-couple influences on work–family balance satisfaction: when benefits become threats. Issue 1 (2nd January 2020) - Buchanan, Tom; Das, Anupam; McFarlane, Adian
ABSTRACT: Using the 2010 General Social Survey in Time Use (Canadian time diary data, N  = 1785), we explore the impact of spouses' time spent on childcare and other work–family factors on parents' work–family balance satisfaction. We examine how benefits compare to threats to parenting time and the relative impact on satisfaction with work–family balance. Our findings indicate that benefits to parenting time (working regular shift, fewer hours, and flextime) increase work–family balance. Threats to parenting (hiring of childcare, spouse's household labour), which should benefit work–family balance, decrease satisfaction. We find mothers' satisfaction with work–family balance is unaffected by increased childcare time spent by fathers. In contrast, mothers' increased childcare time is associated with lower satisfaction with work–family balance for fathers. We argue Canadian fathers may be feeling increased cultural pressure to participate more fully in parenting. Fathers potentially perceive mothers' predominant parenting as a threat to new expectations while mothers perceive fathers' new expectations as a benefit. Alternatively, fathers may feel neglected as a result of mothers' focus on parenting.